Strategi Komunikasi Interpersonal Frontliner dalam Membangun Loyalitas Pelanggan di Naughty Accessories Mall Karawang Central Plaza - Indri Karisa Putri; Firdaus Yuni Dharta; Tikka Muslimah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to examine the interpersonal communication strategies applied by frontliners at Naughty Accessories Mall Karawang Central Plaza in building customer loyalty. The research is motivated by the increasing customer demand for excellent service and the intense competition among brands in the retail accessories industry. The method used is a descriptive qualitative approach with in-depth interview techniques and participatory observation. The results show that the interpersonal communication strategy, which includes Joseph DeVito’s five dimensions—openness, empathy, supportiveness, positiveness, and equality—effectively builds emotional closeness, creates comfort, and increases repurchase intensity. Frontliners at Naughty do more than sell products; they create a pleasant shopping experience. This finding is reinforced by Peter Blau's social exchange theory, which explains that loyalty is formed when customers feel the benefits they receive outweigh the sacrifices they make.